FAKTOR PENENTU KEBERHASILAN UKM DI KOTA TANGERANG - Thea Herawati; Rorlen Rorlen; M. Tony Nawawi (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to determine the determinants of the success of small and medium enterprises (SME’s) with various types of businesses. Researched as many as 90 SME’s located in Tangerang City. The sampling technique used was purposive sampling. Data was collected by distributing questionnaires to respondents who were selected as research samples. The analysis technique uses SEM with Smart PLS devices. The results of this study indicate that (1) product innovation has a positive and significant effect on the success of SMEs; (2) Customer service excellence has a positive and significant impact on the success of SMEs; (3) Delivery has a positive and significant effect on the success of SMEs and (4) Brand reputation has a positive and significant effect on the success of SMEs. The results of the analysis in this study also show that 75% of the variance of SME success is influenced by product innovation, customer service excellence, delivery and brand reputation. Keywords: Product innovation, reliable delivery, Brand reputation SME success